Analysis of the Effect of Population and Average Net Wage/Salary on the Number of Poverty in Medan Using Linear Regression Method - Marpaung, TJ; Tarigan, E.D.; Marpaung, Rony Genevent; Marpaung, J.L. (Journal of Mathematics Technology and Education, 2023)
In this study, the total population along with the average net salary was selected for poverty. The data information used in this study is data derived from agencies. In obtaining the results of the analysis on the influence of variables, multiple linear regression was used. The interpretation of this study shows that there is a significant influence between population and average net salary on poverty. The larger the population and the smaller the average net wage/salary, the higher the poverty rate. It is hoped that this research will be able to show a framework of what factors influence poverty so that it can be used as a reference to overcome the problem of poverty in Indonesia, especially the city of Medan. This study does not use manual calculations, and aims to analyze the relationship between population (M1) and average wage / net salary (M2) with the amount of poverty (D). The equation D is 221105.0 - 0.0147 M1 + 0.0147 M2, with the value of the influence of M1 and M2 on D amounting to 0.341.